Bioactive glass/polymer composite scaffolds mimicking bone tissue - Gentile, Piergiorgio (2012)
The aim of this work was the preparation and characterization of scaffolds with mechanical and functional properties able to regenerate bone. Porous scaffolds made of chitosan/gelatin (POL) blends containing different amounts of a bioactive glass (CEL2), as inorganic material stimulating biomineralization, were fabricated by freeze-drying. Foams with different compositions (CEL2/POL 0/100; 40/60; 70/30 wt %/wt) were prepared. Samples were crosslinked using genipin (GP) to improve mechanical strength and thermal stability. The scaffolds were characterized in terms of their stability in water, chemical structure, morphology, bioactivity, and mechanical behavior. Moreover, MG63 osteoblast-like cells and periostealderived stem cells were used to assess their biocompatibility. CEL2/POL samples showed interconnected pores having an average diameter ranging from 179 6 5 lm for CEL2/POL 0/ 100 to 136 6 5 lm for CEL2/POL 70/30. GP-crosslinking and the increase of CEL2 amount stabilized the composites to water solution (shown by swelling tests). In addition, the SBF soaking experiment showed a good bioactivity of the scaffold with 30 and 70 wt % CEL2. The compressive modulus increased by increasing CEL2 amount up to 2.1 6 0.1 MPa for CEL2/POL 70/30. Dynamical mechanical analysis has evidenced that composite scaffolds at low frequencies showed an increase of storage and loss modulus with increasing frequency; furthermore, a drop of E0 and E00 at 1 Hz was observed, and for higher frequencies both moduli increased again. Cells displayed a good ability to interact with the different tested scaffolds which did not modify cell metabolic activity at the analyzed points. MTT test proved only a slight difference between the two cytotypes analyzed.